PENGARUH PROSES ASUHAN GIZI TERSTANDAR BERBASIS SKRINING GIZI TERHADAP OUTCOME PASIEN DI RUMAH SAKIT - , Susetyowati, DCN., M.Kes, Prof. dr. Hamam Hadi., MS.Sc.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: A comprehensive nutrition assessment needs to be done for all hospitalized patients. The accuracy of nutritional assessment is necessary to ensure the provision of optimal nutrition support for the patient to prevent iatrogenic malnutrition and speed up the healing process. Nutritional screening which not only can be assessed by dietitian is an important part of Standardized Nutrition Care Process (SNCP). However, integration between the application and SNCP remains unclear, namely due to the absence of guidelines for nutrition intervention for patients at risk of malnutrition. Objective: To develop a simple, quick and valid nutrition screening tool (NST) that can be used to identify adult patients at risk of malnutrition, and to determine the effect of nutritional care process to improved nutritional intake, nutritional status (MUAC, albumin levels), length of stay, and discharge status of patients. Methods: An observational study was developed for assessing the new NST in the first study and the second phase of the study using a 2x2 factorial design. The subjects were 495 adult patients admitted to Sardjito General Hospital Yogyakarta, excluding maternity, and psychiatric patients. The validity of the new nutritional screening tool will be tested by measuring the sensitivity and specificity value compared to Subjective Global Assessment. A total of 480 people were divided into 4 treatment groups which are: screened with Nutritional Risk Screening (NRS) and get hospital-based SNCP (A1B1)